TRANSLATING AS A PURPOSEFUL ACTIVITY:A PROSPECTIVE APPROACH - Christiane Nord (TEFLIN, 2006)
Taking a prospective approach to translation, translators choose their translation strategies according to the purpose or function the translated text is intended to fulfill for the target audience. Since communicative purposes need certain conditions in order to work, it is the translators task to analyze the conditions of the target culture and to decide whether, and how, the source-text purposes can work for the target audience according to the specifications of the translation brief. If the target-culture conditions differ from those of the source culture, there are usually two basic options: either to transform the text in such a way that it can work under target-culture conditions (= instrumental translation), or to replace the source-text functions by their respective meta-functions (= documentary translation).